(untitled) (Baghdad Science Journal, 2022)
This study investigated the outcome of Alstonia boonei stem bark on liver enzymes after inducing the Wistar albino rats with carbon tetrachloride (CCl4). This effect of plant extract was compared with silymarin – a drug commonly used for the treatment of chronic hepatocyte disorder. The plant sample was extracted with ethanol; acute toxicity study of the extract was performed on eighteen Wistar mice, while 30 rats were sacrificed for liver enzymes assay. The rats were divided into six clusters: each cluster has five rats, culster 1 served as control and was given 2 mL/kg b.w - distilled water; clusters 2 – 6 were CCl4 induced. Cluster 2 was untreated but served as the negative control while cluster 3 was given 0.025 mL or 25kg/kg B.W of Silymarin, which was a regular medicine and aided as the ordinary control. Rats in clusters 4 – 6 were administered - 100, 200 and 500 mg/kg, respectively of ethanol extract for fourteen days. The acute toxicity results of A. boonei extract showed relative fortification due to no death or adversarial responses after 24 hours of the extract administration. A substantial (P ≥ 0.05) surge in ALT action after administering 500 mg/kg proves lesser toxicity was greater dosage. At low dosage of the extract, a non-significant (p ≥ 0.05) rise in AST action specifies that the extract was moderately harmless with no hepatotoxic magnitude at low medication. The substantial reduction of alkaline phosphatase action in cluster 3 rats induced with CCl4 and given with Silymarin, together with clusters 4 – 6 that were CCl4 induced and administered with graded doses of A. boonei stem bark extract suggest hepatoprotective properties.